A note on an extended fuzzy bi-level optimization approach for water exchange in eco-industrial parks with hub topology - Tan, Raymond Girard R. (Animo Repository, 2011)
In our previous paper, a fuzzy bi-level programming model was developed to determine optimal interplant water integration networks in eco-industrial parks (EIPs). This approach allowed the appropriate incentive mechanisms, in the form of fresh water and effluent fees as well as water reuse subsidies, to be optimized from the perspective of the EIP authority. This work extends the original mathematical model by modifying the role of the EIP authority to include water regeneration and redistribution via a centralized hub. The resulting fuzzy bi-level programming model may then be solved to yield a "satisficing" solution that reflects a reasonable compromise between the EIP authority's desire to minimize fresh water usage, and the participating companies' desire to minimize costs. A case study is used to illustrate the modeling approach.